(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Diabetes mellitus is characterized by persistently high blood sugar levels, and Glibenclamide is commonly used to manage these levels. Pulsatile formulations of Glibenclamide offer controlled timed release to address early morning hyperglycemia, enhancing glucose management and reducing complications. Incorporating Aloe barbadensis miller spray-dried powder as a solid plug in the pulsatile capsule design may help control morning glucose spikes and reduce elevated triglyceride levels in diabetic patients. The present study utilized the Pulsincap® system, which incorporates ethyl cellulose (EC)–coated capsules containing optimized glibenclamide tablets and a swellable plug. Solid dispersions (SDs) were developed using Soluplus® to enhance the poor aqueous solubility of glibenclamide, with compatibility confirmed via Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). Capsules (size ‘000’), coated with 10% w/v ethyl cellulose in methanol and dibutyl phthalate solution, achieved sustained release over 12 hrs. Immediate-release (IR) tablets, formulated via wet granulation, exhibited rapid disintegration within 2 mins. Sustained-release (SR) tablets, optimized using a 3² full factorial design with varying concentrations of HPMC K4M and HPMC K100M CR, demonstrated release profiles of 16-37% at 1 hr, 33-74% at 4 hrs, and 44-100% at 8 hrs. The erodible plug, composed of HPMC K15M, guar gum, and aloe vera, provided swelling and controlled lag times ranging from 7 to 12 hrs. The pulsatile delivery system effectively enhanced glibenclamide bioavailability and modulated its release, offering potential improvements in glycemic management for diabetic patients.